PENGARUH MODEL RADEC TERHADAP KEMAMPUAN LITERASI SAINS SISWA KELAS IV SDN SUKODONO II (MATERI: WUJUD ZAT DAN PERUBAHANNYA) - Maghfiroh; Muhammad Assegaf Baalwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study investigates the impact of the RADEC (Read, Answer, Discuss, Explain, Create) learning model on the science literacy skills of fourth-grade students at SDN Sukodono II. The research was motivated by students' difficulties in understanding the states of matter due to conventional teaching methods and limited use of interactive media. A pre-experimental one-group pretest-posttest design was employed involving 30 students. The literacy test was developed based on PISA indicators and validated using expert judgment and Cronbach’s Alpha (α = 0.771). Data analysis using the Paired Sample T-Test showed a statistically significant difference between pretest (M = 10.47, SD = 3.15) and posttest (M = 15.83, SD = 4.50) scores, with t(29) = -8.781, p < 0.001. The results indicate that the RADEC model significantly improves students’ science literacy. This model is recommended as an effective, interactive, and contextual learning strategy for primary education.